Dissolution profiles of perindopril and indapamide in their fixed-dose formulations by a new HPLC method and different mathematical approaches - Gumieniczek Anna; Mączka Paulina; Komsta Łukasz; Pietraś Rafał (Acta Pharmaceutica)
A new HPLC method was introduced and validated for simultaneous determination of perindopril and indapamide. Validation procedure included specificity, sensitivity, robustness, stability, linearity, precision and accuracy. The method was used for the dissolution test of perindopril and indapamide in three fixed-dose formulations. The dissolution procedure was optimized using different media, different pH of the buffer, surfactants, paddle speed and temperature. Similarity of dissolution profiles was estimated using different model-independent and model-dependent methods and, additionally, by principal component analysis (PCA). Also, some kinetic models were checked for dissolved amounts of drugs as a function of time.